Parenting Strategies for Eating and Activity Scale (PEAS): Turkish validity and reliability study - Sinan, Ozlem; Kucuk, Sibel; Tosun, Betul; Uludasdemir, Dilek; Kucuk, Mihran (Progress in Nutrition, 2019)
The aim of this research was to determine Turkish validity and reliability of the Parenting Strategies for Eating and Activity Scale (PEAS). The study group consisted of 1004 parents, who had children at the ages of 6-12 years old and were referred to the children’s health and diseases service of a state hospital. The PEAS and the Child-Feeding Questionnaire (CFQ) that is used to measure structure validity were used to collect data. The PEAS consists of five sub-dimensions and 26 items. Internal consistency coefficient and item-total score correlation coefficients of the subscales of the PEAS were calculated for the reliability analysis. Scope and structure validity analyses were conducted for validity. A moderate and more than positive correlation was found between the scores of all sub-dimensions in the structural validity analysis. The correlation between the scores obtained from the PEAS and the CFQ scale was found to be significant in the criterion validity analysis. Cronbach’s alpha reliability coefficient value was 0.91. This study showed that the PEAS is a valid and reliable measurement tool to measure parental approaches toward nutrition and activities of children in Turkey. PEAS is suggested to be used by the healthcare professionals working with children and their families to determine the factors related to the parents’ approaches regarding children’s nutrition and activities.